Binder for solid electrolyte battery, slurry, electrode, and solid electrolyte battery

By using multi-stage polymer as the adhesive, combining the characteristics of segment A and segment B, and introducing fluoride units, the adhesion and toughness of the solid electrolytic layer or electrode material layer in the solid-state battery is solved, and a high-performance solid-state battery layer structure is achieved.

JP2025037855AActive Publication Date: 2025-03-18DAIKIN INDUSTRIES LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024154340
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-09-06
Publication Date
2025-03-18
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The prior art is difficult to form a solid electrolytic layer or electrode material layer with excellent adhesion and toughness but without lack of flexibility in solid-state batteries, especially in the presence of bending and tensile stresses during the manufacturing process.

Method used

A multi-stage polymer is used as the binder, which comprises segment A and segment B, wherein the glass transition temperature of segment A is below 25°C, the melting point of segment B is above 50°C, and fluoride units are introduced into the polymer to improve fire resistance and thermal stability.

Benefits of technology

The excellent adhesion, toughness and flexibility of the solid electrolytic layer or electrode material layer in the solid-state battery is achieved, and the performance can be maintained under bending and tensile stresses is achieved, which improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037855000001
    Figure 2025037855000001
Patent Text Reader

Abstract

To provide a binder for a solid electrolyte battery which can form one of a solid electrolyte layer and an electrode material layer which have an excellent adhesive property and toughness.SOLUTION: There is provided a binder for a solid electrolyte battery including a polymer, the binder including a segment A with a glass transition temperature of at least 25°C and a segment B with a melting point of at least 50°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a binder for a solid electrolyte battery, a slurry, an electrode, and a solid electrolyte battery. [Background technology]

[0002] Patent Document 1 describes a binder used in a slurry for a solid battery containing sulfide-based solid electrolyte particles, the binder having a resin terminal functional group 0.01≦([-CH2OH]+[-COOH]) / ([-CH3]+[-CF2H]+[-CH2OH]+[-CH2I]+[-OC(O)RH]+[-COOH]≦0.25 (In the formula, R represents an alkyl group having 1 to 20 carbon atoms.) The binder is characterized by containing a fluorine-containing elastomer that satisfies the above.

[0003] Patent Document 2 describes a binder used in a slurry for a solid battery containing sulfide-based solid electrolyte particles, the binder comprising a polymer having vinylidene fluoride units and at least one copolymerization unit (A) selected from the group consisting of monomer units having a structure represented by the following general formula (1) and monomer units having a structure represented by the following general formula (2): General formula (b1):-(CH2-CFRf1)- General formula (b2):-(CHF-CHRf2)- In the formula, Rf1 and Rf2 are linear or branched fluorinated alkyl or fluorinated alkoxy groups having 1 to 12 carbon atoms, and when the number of carbon atoms is 2 or more, they may contain an oxygen atom between carbon atoms. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2021 / 015230 [Patent Document 2] International Publication No. 2021 / 015229 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a binder for solid electrolyte batteries that can form a solid electrolyte layer or an electrode material layer that is excellent in adhesion and toughness. [Means for solving the problem]

[0006] According to the present disclosure, there is provided a binder for solid electrolyte batteries, which contains a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more. Effect of the Invention

[0007] According to the present disclosure, it is possible to provide a binder for a solid electrolyte battery, which is capable of forming a solid electrolyte layer or an electrode material layer having excellent adhesion and toughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Specific embodiments of the present disclosure will be described in detail below, but the present disclosure is not limited to the following embodiments.

[0009] A solid electrolyte battery is known that includes a positive electrode material layer, a negative electrode material layer, and a solid electrolyte layer formed between the positive electrode material layer and the negative electrode material layer. Since bending stress is applied to the solid electrolyte layer and the electrode material layer of the electrode, the binder used to form the solid electrolyte layer and the electrode material layer is required to have a property that can provide a solid electrolyte layer and an electrode material layer that are excellent in flexibility and can withstand bending stress. Patent Document 1 proposes a binder that is characterized by including a fluorine-containing elastomer as a binder with excellent flexibility.

[0010] The solid electrolyte layer and the electrode material layer formed using the binder described in Patent Document 1 have sufficient flexibility to prevent cracking. On the other hand, in some battery manufacturing methods, not only bending stress but also tension is applied to the solid electrolyte layer and the electrode material layer. The present inventors have found that if not only flexibility but also toughness can be imparted to the solid electrolyte layer and the electrode material layer used in such manufacturing methods, a battery exhibiting high performance can be manufactured.

[0011] The binder for solid electrolyte batteries according to the present disclosure has been developed in consideration of such current circumstances, and by using the binder for solid electrolyte batteries according to the present disclosure, it is possible to form a solid electrolyte layer or an electrode material layer having excellent toughness without impairing excellent flexibility.

[0012] In the present disclosure, the flexibility and toughness of the solid electrolyte layer and the electrode material layer can be confirmed, for example, by performing a three-point bending test on a test laminate including a solid electrolyte layer and a transfer sheet, or an electrode including an electrode material layer. A solid electrolyte layer of a test laminate having a small maximum test force measured by a three-point bending test, or an electrode material layer of an electrode, can be said to have excellent flexibility. In addition, a solid electrolyte layer of a test laminate having a large half-width measured by a three-point bending test, or an electrode material layer of an electrode, can be said to have excellent toughness. The half-width can be determined as the peak width at half the stress of the peak stress by drawing a curve with the stroke of the autograph as the horizontal axis and the stress as the vertical axis using the results of the three-point bending test.

[0013] Furthermore, the solid electrolyte layer and the electrode material layer obtained by using the binder for solid electrolyte batteries of the present disclosure have excellent adhesion to metal foils, and therefore, even when bent, the solid electrolyte layer and the electrode material layer obtained by using the binder for solid electrolyte batteries of the present disclosure are sufficiently adhered to other layers and are not easily peeled off.

[0014] That is, according to the present disclosure, there is provided a binder for solid electrolyte batteries (hereinafter, sometimes referred to as a first binder for solid electrolyte batteries) containing a polymer including a segment A having a glass transition temperature of 25°C or less and a segment B having a melting point of 50°C or more.

[0015] The present disclosure also provides a binder for solid electrolyte batteries that contains a polymer, the polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount of 5 mass% or less at 25°C (hereinafter, sometimes referred to as a second binder for solid electrolyte batteries).

[0016] In the present disclosure, a solid electrolyte is a solid electrolyte and is distinguished from a liquid electrolyte (non-aqueous electrolyte). The solid electrolyte includes a polymer electrolyte and an inorganic solid electrolyte. The binder for a solid electrolyte battery of the present disclosure can be suitably used in particular as a binder for an inorganic solid electrolyte battery or an all-solid-state battery.

[0017] First, the configuration of the first binder for solid electrolyte batteries will be described in detail.

[0018] 1. First binder for solid electrolyte batteries The first binder for solid electrolyte batteries contains a polymer including a segment A and a segment B. As long as the polymer includes a segment A and a segment B, the polymer may include another segment having a different structure from the segments A and B.

[0019] (Polymer segment A) Segment A has a glass transition temperature of 25° C. or lower. The glass transition temperature of segment A is preferably 0° C. or lower, more preferably −5° C. or lower, and even more preferably −10° C. or lower. Since the first binder for solid electrolyte batteries contains a polymer including segment A having a glass transition temperature, it is possible to form a solid electrolyte layer or an electrode material layer having flexibility that is not significantly inferior to that when a conventional binder is used.

[0020] The glass transition temperature can be determined by obtaining a DSC curve using a differential scanning calorimeter (DSC822e, Mettler Toledo, or X-DSC7000, Hitachi High-Tech Science) by cooling 10 mg of a sample to -75°C and then heating at 20°C / min, and determining the glass transition temperature as the temperature at the intersection of an extension of the baseline before and after the second-order transition of the DSC curve and a tangent to the inflection point of the DSC curve.

[0021] The heat of fusion of segment A is preferably less than 5 J / g, more preferably less than 3 J / g, and even more preferably less than 2 J / g, because this can further improve the flexibility of the solid electrolyte layer or the electrode material layer.

[0022] The heat of fusion can be calculated from the magnitude of the melting peak (ΔH) of the endothermic curve obtained by heating a sample from 30° C. to 220° C. at a rate of 10° C. / min using a differential scanning calorimetry (DSC) device. When a polymer does not show a clear melting peak, the polymer has no heat of fusion, that is, the heat of fusion of the polymer is 0 J / g.

[0023] Segment A may be a segment that does not exhibit a distinct melting point.

[0024] Segment A preferably contains a fluorine-containing monomer unit because it can improve the flame retardancy and heat resistance of the solid electrolyte layer and the electrode material layer. The fluorine-containing monomer that can constitute segment A is not particularly limited as long as it is a monomer containing a fluorine atom, and examples thereof include vinylidene fluoride [VdF], trifluoroethylene, tetrafluoroethylene [TFE], hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, vinyl fluoride, a monomer that gives a repeating unit represented by general formula (b1) described later, and a monomer that gives a repeating unit represented by general formula (b2) described later.

[0025] The content of the fluorine-containing monomer unit in Segment A is preferably 50 mol % or more, more preferably 90 mol % or more, and even more preferably 99 mol % or more, and is preferably 100 mol % or less, and may be 100 mol %, based on all monomer units constituting Segment A.

[0026] Segment A may further contain a non-fluorine-containing monomer unit. Examples of the non-fluorine-containing monomer include ethylene, propylene, and alkyl vinyl ether. The content of the non-fluorine-containing monomer unit is preferably 0 to 50 mol%, more preferably 0 to 10 mol%, and even more preferably 0 to 1 mol%, based on the total monomer units constituting segment A, and may be 0 mol%.

[0027] Segment A may further contain units based on a monomer having a reactive group such as a cyano group, a carboxyl group, an alkoxycarbonyl group, I, Br, -CHOH, a carbon-carbon double bond, etc. The content of units based on a monomer having a reactive group is preferably 0 to 50 mol %, more preferably 0 to 10 mol %, and even more preferably 0 to 1 mol %, relative to all monomer units constituting segment A, and may be 0 mol %.

[0028] In the present disclosure, the content of each monomer unit can be measured by NMR.

[0029] Segment A preferably contains at least a VdF unit or a TFE unit as a fluorine-containing monomer unit, and more preferably contains at least a VdF unit. By containing a VdF unit in segment A, the glass transition temperature of segment A can be easily adjusted within a desired range, and the flexibility of the solid electrolyte layer or the electrode material layer can be further improved. In addition, by containing a VdF unit in segment A, the solubility of the binder in a solvent such as butyl butyrate can be improved.

[0030] The content of VdF units in segment A is preferably 99 to 15 mol%, more preferably 94 mol% or less, even more preferably 88 mol% or less, still more preferably 82 mol% or less, particularly preferably 80 mol% or less, more preferably 22 mol% or more, even more preferably 50 mol% or more, still more preferably 60 mol% or more, and particularly preferably 70 mol% or more, based on all monomer units constituting segment A.

[0031] It is more preferable that segment A contains at least one selected from the group consisting of a VdF unit and a repeating unit represented by any one of the following formulas, since this can further improve the flexibility of the solid electrolyte layer or the electrode material layer and can further improve the solvent solubility of the binder in a solvent such as butyl butyrate: Formula:-CF2-CF[-CF3]- General formula (b1):-CH2-CFRf 1 - (In the formula, Rf 1 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms. General formula (b2):-CHF-CHRf 2 - (In the formula, Rf 2 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms.

[0032] The content of at least one unit selected from the group consisting of repeating units represented by any of the above formulas in Segment A is preferably 1 to 85 mol%, more preferably 6 mol% or more, even more preferably 12 mol% or more, still more preferably 18 mol% or more, particularly preferably 20 mol% or more, more preferably 78 mol% or less, even more preferably 50 mol% or less, still more preferably 40 mol% or less, and particularly preferably 30 mol% or less, based on all monomer units constituting Segment A.

[0033] The repeating unit represented by the formula: -CF2-CF[-CF3]- is a repeating unit based on hexafluoropropylene. Thus, in one embodiment, segment A contains a VdF unit and a hexafluoropropylene unit.

[0034] General formula (b1):-CH2-CFRf 1 - In Rf 1 is a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms, or a linear or branched fluorinated alkoxy group having 1 to 12 carbon atoms. When the fluorinated alkyl group and the fluorinated alkoxy group each have 2 or more carbon atoms, they can contain an oxygen atom (-O-) between carbon atoms.

[0035] Rf 1 The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 1In the fluorinated alkyl group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferred that the fluorinated alkyl group does not contain any substituent other than a fluorine atom.

[0036] Rf 1 The fluorinated alkoxy group of Rf may be a partially fluorinated alkoxy group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkoxy group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 1 In the fluorinated alkoxy group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferable that the fluorinated alkoxy group does not contain any substituent other than a fluorine atom.

[0037] Rf 1 The number of carbon atoms is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and particularly preferably 1.

[0038] Rf 1 The general formula: -(Rf 11 ) m -(O) p -(Rf 12 -O) n -Rf 13 (In the formula, Rf 11 and Rf 12 Rf independently represents a linear or branched fluorinated alkylene group having 1 to 4 carbon atoms; 13 is a linear or branched fluorinated alkyl group having 1 to 4 carbon atoms, p is 0 or 1, m is an integer of 0 to 4, and n is an integer of 0 to 4).

[0039] Rf 11 and Rf 12 The fluorinated alkylene group of Rf may be a partially fluorinated alkylene group in which some of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms, or may be a perfluorinated alkylene group in which all of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms. 11 and Rf12 The fluorinated alkylene group of Rf may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom. 11 and Rf 12 may be the same or different in each occurrence.

[0040] Rf 11 Examples of the fluorinated alkylene group include, -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF2-CF2-, -CF2-CF2-CF2-CF2-CF2-, -CH(CF3)-CF2-CF2-, -CF(CF3)-CF2-CF2-, -CF2-CF2-CF2-, -C(CF3)2-CF2- and the like. Among these, perfluorinated alkylene groups having 1 or 2 carbon atoms are preferred, and -CF2- is more preferred.

[0041] Rf 12 Examples of the fluorinated alkylene group include, -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF Among these, perfluorinated alkylene groups having 1 to 3 carbon atoms are preferred, and -CF2-, -CF2CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2- or -CF2-CF(CF3)- is more preferred.

[0042] Rf 13The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 13 The fluorinated alkyl group may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom (for example, a reactive functional group such as -CN, -I, or -Br).

[0043] Rf 13 Examples of the fluorinated alkyl group include, -CH2F, -CHF2, -CF3, -CH2-CH2F, -CH2-CHF2, -CH2-CF3, -CHF-CH2F, -CHF-CHF2, -CHF-CF3, -CF2-CH2F, -CF2-CHF2, -CF2-CF3, -CH2-CF2-CH2F, -CHF-CF2-CH2F, -CF2-CF2-CH2F, -CF(CF3)-CH2F, -CH2-CF2-CHF2, -CHF-CF2-CHF2, -CF2-CF2-CHF2, -CF(CF3)-CHF2, -CH2-CF2-CF3, -CHF-CF2-CF 3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CH2-CF2-CF2-CF3, -CHF-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, -CF(CF3)-CF2-CF3, -C(CF3)2-CF3, and the like are included, and among these, -CF3, -CHF-CF3, -CF2-CHF2, -CF2-CF3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, and -CF(CF3)-CF2-CF3 are preferred.

[0044] As p, 0 is preferable.

[0045] m is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. In addition, when p is 0, m is preferably 0 as well.

[0046] n is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0.

[0047] The repeating unit represented by formula (b1) is -CH2-CF[-CF3]-, -CH2-CF[-CF2CF3]-, -CH2-CF[-CF2CF2CF3]-, -CH2-CF[-CF2CF2CF2CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CHF-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CF2-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CF(CF3)-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CH(CF3)-CF2-CF3]-, -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CF(CF3)-CF2-CF3]-, -CH2-CF[-OCF2OCF3]-, -CH2-CF[-OCF2CF2CF2OCF3]-, -CH2-CF[-CF2OCF2OCF3]-, -CH2-CF[-CF2OCF2CF2CF2OCF3]-, or -CH2-CF[-O-CF2-CF3]- is preferred, -CH2-CF[-CF3]-, or -CH2-CF[-CF2-O-CF(CF3)-CF2-O-CHF-CF3]-, is more preferred.

[0048] General formula (b2):-CHF-CHRf 2 - In Rf 2is a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms, or a linear or branched fluorinated alkoxy group having 1 to 12 carbon atoms. When the fluorinated alkyl group and the fluorinated alkoxy group each have 2 or more carbon atoms, they can contain an oxygen atom (-O-) between carbon atoms.

[0049] Rf 2 The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 2 In the fluorinated alkyl group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferred that the fluorinated alkyl group does not contain any substituent other than a fluorine atom.

[0050] Rf 2 The fluorinated alkoxy group of Rf may be a partially fluorinated alkoxy group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkoxy group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 2 In the fluorinated alkoxy group, a hydrogen atom may be substituted with a substituent other than a fluorine atom, but it is preferable that the fluorinated alkoxy group does not contain any substituent other than a fluorine atom.

[0051] Rf 2 The number of carbon atoms is preferably 1 to 10, more preferably 1 to 6, further preferably 1 to 4, and particularly preferably 1.

[0052] Rf 2 The general formula: -(Rf 21 ) m -(O) p -(Rf 22 -O) n -Rf 23 (In the formula, Rf 21 and Rf 22Rf independently represents a linear or branched fluorinated alkylene group having 1 to 4 carbon atoms; 23 is a linear or branched fluorinated alkyl group having 1 to 4 carbon atoms, p is 0 or 1, m is an integer of 0 to 4, and n is an integer of 0 to 4.

[0053] Rf 21 and Rf 22 The fluorinated alkylene group of Rf may be a partially fluorinated alkylene group in which some of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms, or may be a perfluorinated alkylene group in which all of the hydrogen atoms bonded to the carbon atoms are replaced with fluorine atoms. 21 and Rf 22 The fluorinated alkylene group of Rf may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom. 21 and Rf 22 may be the same or different in each occurrence.

[0054] Rf 21 Examples of the fluorinated alkylene group include, -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF2-CF2-, -CF2-CF2-CF2-CF2-CF2-, -CH(CF3)-CF2-CF2-, -CF(CF3)-CF2-CF2-, -CF2-CF2-CF2-, -C(CF3)2-CF2- and the like. Among these, perfluorinated alkylene groups having 1 or 2 carbon atoms are preferred, and -CF2- is more preferred.

[0055] Rf 22Examples of the fluorinated alkylene group include, -CHF-, -CF2-, -CH2-CF2-, -CHF-CF2-, -CF2-CF2-, -CF(CF3)-, -CH2-CF2-CF2-, -CHF-CF2-CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2-, -CF2-CF(CF3)-, -C(CF3)2-, -CH2-CF2-CF2-CF2-, -CHF-CF2-CF Among these, perfluorinated alkylene groups having 1 to 3 carbon atoms are preferred, and -CF2-, -CF2CF2-, -CF2-CF2-CF2-, -CF(CF3)-CF2- or -CF2-CF(CF3)- is more preferred.

[0056] Rf 23 The fluorinated alkyl group of Rf may be a partially fluorinated alkyl group in which some of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms, or a perfluorinated alkyl group in which all of the hydrogen atoms bonded to the carbon atom are replaced with fluorine atoms. 23 The fluorinated alkyl group may have a hydrogen atom substituted with a substituent other than a fluorine atom, but preferably does not contain any substituent other than a fluorine atom (for example, a reactive functional group such as -CN, -I, or -Br).

[0057] Rf 23Examples of the fluorinated alkyl group include, -CH2F, -CHF2, -CF3, -CH2-CH2F, -CH2-CHF2, -CH2-CF3, -CHF-CH2F, -CHF-CHF2, -CHF-CF3, -CF2-CH2F, -CF2-CHF2, -CF2-CF3, -CH2-CF2-CH2F, -CHF-CF2-CH2F, -CF2-CF2-CH2F, -CF(CF3)-CH2F, -CH2-CF2-CHF2, -CHF-CF2-CHF2, -CF2-CF2-CHF2, -CF(CF3)-CHF2, -CH2-CF2-CF3, -CHF-CF2-CF 3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CH2-CF2-CF2-CF3, -CHF-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, -CF(CF3)-CF2-CF3, -C(CF3)2-CF3, and the like are included, and among these, -CF3, -CHF-CF3, -CF2-CHF2, -CF2-CF3, -CF2-CF2-CF3, -CF(CF3)-CF3, -CF2-CF2-CF2-CF3, -CH(CF3)-CF2-CF3, and -CF(CF3)-CF2-CF3 are preferred.

[0058] As p, 0 is preferable.

[0059] m is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0. In addition, when p is 0, m is preferably 0 as well.

[0060] n is preferably an integer of 0 to 2, more preferably 0 or 1, and further preferably 0.

[0061] The repeating unit represented by formula (b2) is -CHF-CH[-CF3]-, -CHF-CH[-CF2CF3]-, -CHF-CH[-CF2CF2CF3]-, or -CHF-CH[-CF2CF2CF2CF3]-, is preferred, -CHF-CH[-CF3]- is more preferred.

[0062] In particular, it is preferable that segment A contains a VdF unit and a 2,3,3,3-tetrafluoropropene unit. By containing a VdF unit and a 2,3,3,3-tetrafluoropropene unit in segment A, the flexibility of the solid electrolyte layer or the electrode material layer can be further improved. In addition, the solubility of the binder in a solvent such as butyl butyrate can be improved.

[0063] The content of 2,3,3,3-tetrafluoropropene units in Segment A is preferably 1 to 85 mol%, more preferably 6 mol% or more, even more preferably 12 mol% or more, still more preferably 18 mol% or more, particularly preferably 20 mol% or more, more preferably 78 mol% or less, even more preferably 50 mol% or less, still more preferably 40 mol% or less, and particularly preferably 30 mol% or less, based on all monomer units constituting Segment A.

[0064] In one embodiment, segment A may be formed by a 2,3,3,3-tetrafluoropropene / VdF copolymer or a 2,3,3,3-tetrafluoropropene / VdF / TFE copolymer.

[0065] In the 2,3,3,3-tetrafluoropropene / VdF copolymer, the composition (mol %) of 2,3,3,3-tetrafluoropropene units / VdF units is preferably (18 to 40) / (82 to 60), and more preferably (20 to 30) / (80 to 70).

[0066] In the 2,3,3,3-tetrafluoropropene / VdF / TFE copolymer, the composition (mol %) of 2,3,3,3-tetrafluoropropene units / VdF units / TFE units is preferably (18 to 40) / (81 to 25) / (1 to 35), and more preferably (20 to 40) / (75 to 30) / (5 to 30).

[0067] In one embodiment, segment A contains 2,3,3,3-tetrafluoropropene units and VdF units, and the content of monomer units other than 2,3,3,3-tetrafluoropropene units and VdF units is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, even more preferably 0 to 1 mol%, still more preferably 0 to 0.1 mol%, and particularly preferably 0 mol%, based on the total monomer units constituting segment A. The content of 2,3,3,3-tetrafluoropropene units and the content of VdF units may be within the above-mentioned ranges.

[0068] (Polymer segment B) Segment B has a melting point of 50° C. or higher. The melting point of segment B is preferably 90° C. or higher, more preferably 140° C. or higher, preferably 240° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The first binder for solid electrolyte batteries contains a polymer including segment B having a melting point in addition to segment A having a glass transition temperature, and therefore can form a solid electrolyte layer or electrode material layer having excellent adhesion and toughness without impairing excellent flexibility.

[0069] The melting point can be determined by using a differential scanning calorimetry (DSC) device to raise the temperature of a sample from 30° C. to 220° C. at a rate of 10° C. / min, and measuring the temperature at the peak of the endothermic curve obtained.

[0070] Typically, the melting point of segment B is the same as the melting point of the first polymer. Therefore, by measuring the melting point of the first polymer, the melting point of segment B in the first polymer can be determined.

[0071] The heat of fusion of segment B is preferably 5 J / g or more, more preferably 10 J / g or more, even more preferably 30 J / g or more, still more preferably 35 J / g or more, and is preferably 90 J / g or less, more preferably 60 J / g or less, and even more preferably 55 J / g or less, because this can further improve the adhesion, flexibility, and toughness of the solid electrolyte layer or the electrode material layer.

[0072] The heat of fusion can be calculated from the magnitude of the melting peak (ΔH) of the endothermic curve obtained by heating a sample from 30° C. to 220° C. at a rate of 10° C. / min using a differential scanning calorimetry (DSC) device.

[0073] Segment B preferably contains a fluorine-containing monomer unit because it can improve the oxidation resistance of the solid electrolyte layer and the electrode material layer. The fluorine-containing monomer that can constitute segment B is not particularly limited as long as it is a monomer containing a fluorine atom, and examples thereof include vinylidene fluoride (VdF), trifluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, and vinyl fluoride.

[0074] The content of the fluorine-containing monomer unit in Segment B is preferably 50 mol % or more, more preferably 90 mol % or more, even more preferably 99 mol % or more, and preferably 100 mol % or less, based on all monomer units constituting Segment B.

[0075] Segment B may further contain a non-fluorine-containing monomer unit. Examples of the non-fluorine-containing monomer include ethylene, propylene, and alkyl vinyl ether. The content of the non-fluorine-containing monomer unit is preferably 0 to 50 mol%, more preferably 0 to 10 mol%, and even more preferably 0 to 1 mol%, based on the total monomer units constituting segment B, and may be 0 mol%.

[0076] Segment B may further contain a unit based on a monomer having a polar group, such as a carbonyl group-containing group, an epoxy group, a hydroxy group, a sulfonic acid group, a sulfate group, a phosphate group, an amino group, an amide group, or an alkoxy group.

[0077] Examples of monomers having a polar group include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinyl acetic acid (3-butenoic acid), 3-pentenoic acid, 4-pentenoic acid, 3-hexenoic acid, and 4-heptenoic acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonic acid esters such as dimethyl methylidene malonate; and vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether. carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylate esters such as acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxyethyl phthalate, acryloyloxypropyl succinate, and methacryloyloxyethyl phthalate; monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester; and the like.

[0078] It is preferable that segment B contains at least VdF units as fluorine-containing monomer units. By containing VdF units in segment B, the melting point of segment B can be easily adjusted within a desired range, and the adhesion and toughness of the solid electrolyte layer or the electrode material layer can be further improved. In addition, by containing VdF units in segment B, the solubility of the binder in a solvent such as butyl butyrate can be improved.

[0079] Segment B may contain, in addition to the VdF unit, other monomer units other than the VdF unit. The other monomers may be either fluorine-containing or non-fluorine-containing monomers, and are preferably fluorine-containing monomers (excluding trifluoroethylene) or non-fluorine-containing monomers.

[0080] Examples of fluorine-containing monomers which can form segment B together with VdF include TFE, hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, and vinyl fluoride.

[0081] Examples of the fluorine-free monomer that can form the segment B together with VdF include ethylene and propylene.

[0082] In addition to the VdF unit, segment B may further contain a unit based on a monomer unit having a polar group such as a carbonyl group-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfate group, a phosphoric acid group, an amino group, an amide group, or an alkoxy group. Examples of the monomer having a polar group are as already mentioned.

[0083] As the other monomer capable of constituting segment B together with VdF, at least one selected from the group consisting of TFE, hexafluoropropylene, 2,3,3,3-tetrafluoropropene, and (meth)acrylic acid is particularly preferred.

[0084] The content of VdF units in segment B can further improve the adhesion and toughness of the solid electrolyte layer or the electrode material layer and further improve the solvent solubility of the binder in a solvent such as butyl butyrate, and therefore the content of VdF units in the total monomer units constituting segment B is preferably 97 mol % or more, more preferably more than 99 mol %, and even more preferably 99.5 mol % or more and may be 100 mol % or less.

[0085] The content of monomer units other than VdF units in segment B can further improve the adhesion and toughness of the solid electrolyte layer or the electrode material layer and further improve the solvent solubility of the binder in a solvent such as butyl butyrate, and is therefore preferably 3 mol % or less, more preferably less than 1 mol %, and even more preferably 0.5 mol % or less, and may be 0 mol % or more, relative to the total monomer units constituting segment B.

[0086] In one embodiment, segment B can be formed by a VdF homopolymer containing only VdF units, or a copolymer containing VdF units and at least one other monomer unit selected from the group consisting of TFE units, hexafluoropropylene units, 2,3,3,3-tetrafluoropropene units, and (meth)acrylic acid units.

[0087] In a copolymer containing VdF units and other monomer units, the composition (mol %) of VdF units / other monomer units is preferably (97.0 to 99.9) / (3.0 to 0.1).

[0088] The polymer contained in the first binder for solid electrolyte batteries may contain another segment C having a different structure from the segments A and B, so long as the polymer contains the segments A and B.

[0089] The polymer contained in the first binder for solid electrolyte batteries may be a block copolymer containing a chain structure represented by any one of the following general formulas. General formula: AB General formula: ABA General formula: BAB General formula: ABC General formula: BAC (In the formula, A represents segment A, B represents segment B, and C represents segment C.)

[0090] The polymer contained in the first binder for solid electrolyte batteries preferably contains a chain structure represented by general formula (1) or general formula (2), because it can form a solid electrolyte layer or an electrode material layer having even more excellent adhesion, flexibility, and toughness, and is easy to manufacture. General formula (1):ABA General formula (2): BAB (In the formula, A represents segment A and B represents segment B.)

[0091] As for the polymer contained in the first binder for solid electrolyte batteries, the mass ratio (A / B) of segment A to segment B is preferably 40 / 60 to 95 / 5, more preferably 50 / 50 or more, even more preferably 60 / 40 or more, and more preferably 90 / 10 or less, from the viewpoint of a balance between excellent flexibility and excellent adhesion and toughness.

[0092] The number average molecular weight (polystyrene equivalent) of the polymer contained in the first binder for solid electrolyte batteries is preferably 20000 to 1500000, more preferably 40000 or more, even more preferably 70000 or more, particularly preferably 140000 or more, more preferably 140000 or less, even more preferably 1200000 or less, and particularly preferably 1100000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0093] The weight average molecular weight (polystyrene equivalent) of the polymer contained in the first binder for solid electrolyte batteries is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, still more preferably 200,000 or more, particularly preferably 500,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0094] The polymer contained in the first binder for solid electrolyte batteries is, for example, (1) A method of preparing a polymer for forming segment B by polymerizing a monomer for forming segment B in the presence of a bromine compound or an iodine compound as a chain transfer agent, and preparing a polymer for forming segment A by polymerizing a monomer for forming segment A in the presence of the polymer for forming segment B; (2) A method of preparing a polymer for forming segment A by polymerizing a monomer for forming segment A in the presence of a bromine compound or an iodine compound as a chain transfer agent, and preparing a polymer for forming segment B by polymerizing a monomer for forming segment B in the presence of the polymer for forming segment A; The above-mentioned manufacturing method can be used.

[0095] When method (1) is used, a polymer is obtained in which segment A is bonded to both ends of a polymer chain forming segment B, that is, a polymer containing a chain structure represented by general formula (1): ABA.

[0096] Furthermore, when method (2) is used, a polymer that forms segment B bonded to both ends of a polymer chain that forms segment A, that is, a polymer containing a chain structure represented by general formula (2): BAB, is obtained.

[0097] In the methods (1) and (2), a bromine compound or an iodine compound is used as a chain transfer agent. By using a bromine compound or an iodine compound, an iodine atom or a bromine atom is introduced into the polymer chain end forming one segment, and serves as a binding site for another segment.

[0098] The polymerization method using a bromine compound or an iodine compound includes, for example, a method in which emulsion polymerization is carried out in an aqueous medium under pressure in the presence of a bromine compound or an iodine compound in a substantially oxygen-free state (iodine transfer polymerization method). Representative examples of the bromine compound or iodine compound to be used include, for example, General formula: R 8 I x Br y (In the formula, x and y are each an integer of 0 to 2, and 1≦x+y≦2 is satisfied; R 8 is a saturated or unsaturated fluorohydrocarbon group or chlorofluorohydrocarbon group having 1 to 16 carbon atoms, or a hydrocarbon group having 1 to 3 carbon atoms, which may contain an oxygen atom).

[0099] Examples of iodine compounds include 1,3-diiodoperfluoropropane, 2-iodoperfluoropropane, 1,3-diiodo-2-chloroperfluoropropane, 1,4-diiodoperfluorobutane, 1,5-diiodo-2,4-dichloroperfluoropentane, 1,6-diiodoperfluorohexane, 1,8-diiodoperfluorooctane, 1,12-diiodoperfluorododecane, 1,16-diiodoperfluorohexadecane, diiodomethane, 1,2-diiodoethane, 1,3-diiodo-n-propane, CF2Br2, BrCF2CF2Br, CF3CFBrCF2Br, CFClBr2, BrCF2CFCl Br, CFBrClCFClBr, BrCF2CF2CF2Br, BrCF2CFBrOCF3, 1-bromo-2-iodoperfluoroethane, 1-bromo-3-iodoperfluoropropane, 1-bromo-4-iodoperfluorobutane, 2-bromo-3-iodoperfluorobutane, 3-bromo-4-iodoperfluorobutene-1, 2-bromo-4-iodoperfluorobutene-1, monoiodomonobromo-substituted benzene, diiodomonobromo-substituted benzene, and (2-iodoethyl) and (2-bromoethyl)-substituted benzene. These compounds may be used alone or in combination with each other.

[0100] Among these, it is preferable to use 1,4-diiodoperfluorobutane, 1,6-diiodoperfluorohexane, and 2-iodoperfluoropropane in terms of polymerization reactivity, crosslinking reactivity, availability, and the like.

[0101] In the above-mentioned production method, the polymerization of the monomer is preferably carried out by emulsion polymerization. In one embodiment, the polymerization of the monomer is carried out in the presence of a polymerization initiator, a surfactant and a solvent.

[0102] The polymerization initiator may be an oil-soluble radical polymerization initiator or a water-soluble radical initiator.

[0103] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and disec-butyl peroxydicarbonate, peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate, dialkyl peroxides such as di-t-butyl peroxide, and the like. In addition, di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluorooctanoyl) peroxide, di(ω-hydro-hexadecafluorononanoyl) peroxide, di(perfluorobutyryl) peroxide, di(perfluparyl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide, di(perfluorononanoyl) peroxide, di(ω-chloro- Representative examples of the perfluoro(or fluorochloro)acyl]peroxides include di(ω-chlorohexafluorobutyryl) peroxide, di(ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorodotriacontafluorodocosanoyl) peroxide.

[0104] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, or sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, or percarbonic acid, t-butyl permaleate, or t-butyl hydroperoxide, etc. A reducing agent such as sulfites may also be contained, and the amount used may be 0.1 to 20 times that of the peroxide.

[0105] The amount of the polymerization initiator to be added is not particularly limited, but may be added all at once, stepwise, or continuously in an amount (for example, several ppm relative to water concentration) at least to the extent that the polymerization rate does not drop significantly. The upper limit is within the range in which the heat of polymerization reaction can be removed from the equipment side.

[0106] The surfactant may be a nonionic surfactant, an anionic surfactant, a cationic surfactant, etc. The amount added (relative to the solvent) is preferably 10 ppm by mass to 20% by mass, more preferably 10 ppm by mass to 10% by mass, further preferably 10 to 5000 ppm by mass, and particularly preferably 50 to 5000 ppm by mass.

[0107] A polymerizable emulsifier may also be used as the surfactant. The polymerizable emulsifier is not particularly limited as long as it is a compound having at least one unsaturated bond and at least one hydrophilic group, and examples thereof include CH2=CFCF2OCF(CF3)CF2OCF(CF3)COONH4, CH2=CFCF2CF(CF3)OCF2CF2COONH4, and CF2=CFOCF2CF(CF3)OCF(CF3)COONH4. The amount of the emulsifier added (relative to the solvent) is preferably 10 to 5000 ppm by mass, more preferably 50 to 5000 ppm by mass.

[0108] The solvent is preferably a solvent that does not have chain transfer properties, and examples of the solvent include water, a mixture of water and a water-soluble organic solvent, and a mixture of water and a water-insoluble organic solvent.

[0109] In the polymerization of the monomer, the polymerization temperature, polymerization pressure and polymerization time may vary depending on the type of solvent and polymerization initiator, but may be -15 to 150°C, atmospheric pressure to 6.5 MPa, and 1 to 24 hours. When an oil-soluble radical polymerization initiator is used as the polymerization initiator, the polymerization temperature is preferably 30 to 95°C. When a water-soluble radical polymerization initiator is used as the polymerization initiator, the polymerization temperature is preferably 0 to 100°C, and more preferably 10 to 95°C.

[0110] When the polymerization of the monomer is carried out by emulsion polymerization, an aqueous dispersion containing the polymer is obtained. In the above-mentioned production method, the polymer in the aqueous dispersion is coagulated, washed with water, dehydrated, and dried to obtain a powder of the polymer. The coagulation can be carried out by adding an inorganic salt such as aluminum sulfate or an inorganic acid to the dispersion, by applying a mechanical shear force to the dispersion, or by freezing the dispersion.

[0111] The polymer contained in the first binder for solid electrolyte batteries can also be produced by using at least 2,3,3,3-tetrafluoropropene as a monomer according to the methods described in JP-A-53-3495 and JP-B-61-49327.

[0112] 2. Second Binder for Solid Electrolyte Batteries The second binder for solid electrolyte batteries according to the present disclosure contains a polymer having a glass transition temperature and a melting point, which contains 2,3,3,3-tetrafluoropropene units and has a tetrahydrofuran extractable amount of 5 mass % or less at 25° C.

[0113] The glass transition temperature of the polymer contained in the second binder for solid electrolyte batteries is preferably 25° C. or lower, more preferably 0° C. or lower, even more preferably −5° C. or lower, and even more preferably −10° C. or lower, and although there is no lower limit, may be −40° C. or higher. Since the second binder for solid electrolyte batteries contains a polymer having a glass transition temperature, it is possible to form a solid electrolyte layer or an electrode material layer having flexibility that is not significantly inferior to that when a conventional binder is used.

[0114] The glass transition temperature can be determined by obtaining a DSC curve using a differential scanning calorimeter (DSC822e, Mettler Toledo, or X-DSC7000, Hitachi High-Tech Science) by cooling 10 mg of a sample to -75°C and then heating at 20°C / min, and determining the glass transition temperature as the temperature at the intersection of an extension of the baseline before and after the second-order transition of the DSC curve and a tangent to the inflection point of the DSC curve.

[0115] The melting point of the polymer contained in the second binder for solid electrolyte batteries is preferably 50° C. or higher, more preferably 90° C. or higher, even more preferably 140° C. or higher, and preferably 240° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The second binder for solid electrolyte batteries contains a polymer having a melting point in addition to having a glass transition temperature, and therefore can form a solid electrolyte layer or an electrode material layer having excellent adhesion and toughness without impairing excellent flexibility.

[0116] The melting point can be determined by using a differential scanning calorimetry (DSC) device to raise the temperature of a sample from 30° C. to 220° C. at a rate of 10° C. / min, and measuring the temperature at the peak of the endothermic curve obtained.

[0117] The tetrahydrofuran extractable amount of the polymer contained in the second binder for solid electrolyte batteries is 5% by mass or less, preferably 4% by mass or less, and more preferably 3% by mass or less. Since the second binder for solid electrolyte batteries contains a polymer with a tetrahydrofuran extractable amount within the above numerical range, it has flexibility that is not significantly inferior to that of a conventional binder, and can form a solid electrolyte layer or an electrode material layer that is also excellent in adhesion and toughness. The lower limit of the tetrahydrofuran extractable amount is not particularly limited, but may be 1% by mass or more or 2% by mass or more.

[0118] The amount of tetrahydrofuran extractables can be measured by a method in which a polymer is immersed in tetrahydrofuran at 25° C. for 24 hours, and the filtered solution is dried and solidified.

[0119] The polymer contained in the second binder for solid electrolyte batteries contains 2,3,3,3-tetrafluoropropene units. Since the second binder for solid electrolyte batteries contains 2,3,3,3-tetrafluoropropene units, it is possible to impart solvent solubility to a solvent such as butyl butyrate to the binder, and it is possible to form a solid electrolyte layer or an electrode material layer having excellent adhesion, flexibility, and toughness.

[0120] The polymer contained in the second binder for solid electrolyte batteries preferably contains a fluorine-containing monomer unit (excluding 2,3,3,3-tetrafluoropropene units). By introducing the fluorine-containing monomer unit into the polymer, the glass transition temperature and melting point of the polymer can be easily adjusted, and a solid electrolyte layer or electrode material layer having even more excellent adhesion, flexibility and toughness can be formed.

[0121] The fluorine-containing monomer capable of constituting the polymer contained in the second binder for solid electrolyte batteries is not particularly limited as long as it is a monomer other than 2,3,3,3-tetrafluoropropene and contains a fluorine atom, and examples of the fluorine-containing monomer include vinylidene fluoride [VdF], trifluoroethylene, tetrafluoroethylene [TFE], hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), chlorotrifluoroethylene, hexafluoroisobutene, and vinyl fluoride.

[0122] The fluorine-containing monomer capable of constituting the polymer contained in the second binder for solid electrolyte batteries is preferably at least one selected from the group consisting of VdF, TFE, hexafluoropropylene, perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether), perfluoro(propyl vinyl ether), and chlorotrifluoroethylene, more preferably at least one selected from the group consisting of VdF and TFE, and even more preferably VdF.

[0123] When the polymer contained in the second binder for solid electrolyte batteries contains a VdF unit as a fluorine-containing monomer unit, the solvent solubility of the binder in a solvent such as butyl butyrate is further improved, and by using the second binder for solid electrolyte batteries, a solid electrolyte layer or an electrode material layer having even more excellent adhesion, flexibility and toughness can be formed.

[0124] The content of 2,3,3,3-tetrafluoropropene units in the polymer contained in the second binder for solid electrolyte batteries is preferably 1 to 65 mol %, more preferably 5 mol % or more, even more preferably 9 mol % or more, still more preferably 12 mol % or more, particularly preferably 14 mol % or more, more preferably 62 mol % or less, even more preferably 40 mol % or less, still more preferably 32 mol % or less, and particularly preferably 24 mol % or less, based on all monomer units constituting the polymer.

[0125] The content of the fluorine-containing monomer unit in the polymer contained in the second binder for solid electrolyte batteries is preferably 99 to 35 mol %, more preferably 95 mol % or less, even more preferably 91 mol % or less, still more preferably 88 mol % or less, particularly preferably 86 mol % or less, more preferably 38 mol % or more, even more preferably 60 mol % or more, still more preferably 68 mol % or more, and particularly preferably 76 mol % or more, based on the total monomer units constituting the polymer.

[0126] The content of VdF units in the polymer contained in the second binder for solid electrolyte batteries is preferably 99 to 35 mol %, more preferably 95 mol % or less, even more preferably 91 mol % or less, still more preferably 88 mol % or less, particularly preferably 86 mol % or less, more preferably 38 mol % or more, even more preferably 60 mol % or more, still more preferably 68 mol % or more, and particularly preferably 76 mol % or more, based on all monomer units constituting the polymer.

[0127] The polymer contained in the second binder for solid electrolyte batteries may further contain a non-fluorine-containing monomer unit. Examples of the non-fluorine-containing monomer include ethylene, propylene, and alkyl vinyl ether. The content of the non-fluorine-containing monomer unit is preferably 0 to 40 mol%, more preferably 0 to 8 mol%, and even more preferably 0 to 1 mol%, and may be 0 mol%, based on the total monomer units constituting the polymer.

[0128] The polymer contained in the second binder for solid electrolyte batteries may further contain units based on a monomer having a reactive group such as a cyano group, a carboxyl group, an alkoxycarbonyl group, I, Br, -CH2OH, a carbon-carbon double bond, etc. The content of the units based on a monomer having a reactive group is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, and even more preferably 0 to 1 mol%, based on the total monomer units constituting the polymer, and may be 0 mol%.

[0129] The polymer contained in the second binder for solid electrolyte batteries may further contain a unit based on a monomer having a polar group such as a carbonyl group-containing group, an epoxy group, a hydroxyl group, a sulfonic acid group, a sulfate group, a phosphate group, an amino group, an amide group, or an alkoxy group.

[0130] Examples of monomers having a polar group include hydroxyalkyl (meth)acrylates such as hydroxyethyl acrylate and 2-hydroxypropyl acrylate; unsaturated monobasic acids such as (meth)acrylic acid, crotonic acid, vinyl acetic acid (3-butenoic acid), 3-pentenoic acid, 4-pentenoic acid, 3-hexenoic acid, and 4-heptenoic acid; unsaturated dibasic acids such as maleic acid, maleic anhydride, citraconic acid, and citraconic anhydride; alkylidene malonic acid esters such as dimethyl methylidene malonate; and vinyl carboxyalkyl ethers such as vinyl carboxymethyl ether and vinyl carboxyethyl ether. carboxyalkyl (meth)acrylates such as 2-carboxyethyl acrylate and 2-carboxyethyl methacrylate; (meth)acryloyloxyalkyl dicarboxylate esters such as acryloyloxyethyl succinate, methacryloyloxyethyl succinate, acryloyloxyethyl phthalate, acryloyloxypropyl succinate, and methacryloyloxyethyl phthalate; monoesters of unsaturated dibasic acids such as maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester; and the like.

[0131] The content of units based on monomers having a polar group is preferably 0 to 10 mol %, more preferably 0 to 2 mol %, and even more preferably 0 to 1 mol %, relative to all monomer units constituting the polymer, and may be 0 mol %.

[0132] In one embodiment, the polymer contained in the second binder for solid electrolyte batteries contains 2,3,3,3-tetrafluoropropene units and fluorine-containing monomer units (excluding 2,3,3,3-tetrafluoropropene units), and the content of monomer units other than 2,3,3,3-tetrafluoropropene units and fluorine-containing monomer units is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, even more preferably 0 to 1 mol%, still more preferably 0 to 0.1 mol%, and particularly preferably 0 mol%, based on the total monomer units constituting the polymer. The content of 2,3,3,3-tetrafluoropropene units and the content of fluorine-containing monomer units may be within the above-mentioned ranges.

[0133] In one embodiment, the polymer contained in the second binder for solid electrolyte batteries contains 2,3,3,3-tetrafluoropropene units and VdF units, and the content of monomer units other than 2,3,3,3-tetrafluoropropene units and VdF units is preferably 0 to 10 mol%, more preferably 0 to 2 mol%, even more preferably 0 to 1 mol%, still more preferably 0 to 0.1 mol%, and particularly preferably 0 mol%, based on the total monomer units constituting the polymer. The content of 2,3,3,3-tetrafluoropropene units and the content of VdF units may be within the above-mentioned ranges.

[0134] The number average molecular weight (polystyrene equivalent) of the polymer contained in the second binder for solid electrolyte batteries is preferably 20000 to 1500000, more preferably 40000 or more, even more preferably 70000 or more, particularly preferably 140000 or more, more preferably 140000 or less, even more preferably 1200000 or less, and particularly preferably 1100000 or less. The number average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0135] The weight average molecular weight (polystyrene equivalent) of the polymer contained in the second binder for solid electrolyte batteries is preferably 50,000 to 3,000,000, more preferably 80,000 or more, even more preferably 100,000 or more, still more preferably 200,000 or more, particularly preferably 500,000 or more, more preferably 2,400,000 or less, even more preferably 2,200,000 or less, and particularly preferably 2,000,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.

[0136] The heat of fusion of the polymer contained in the second binder for solid electrolyte batteries is preferably 1 J / g or more, more preferably 3 J / g or more, even more preferably 5 J / g or more, still more preferably 8 J / g or more, and preferably 40 J / g or less, more preferably 30 J / g or less, and even more preferably 20 J / g or less.

[0137] In one embodiment of the polymer contained in the second binder for solid electrolyte batteries, the polymer contains two or more segments. By forming the polymer from two or more segments, the polymer can be easily given a glass transition temperature and a melting point, and the polymer's glass transition temperature and melting point can be easily adjusted, and the adhesion, flexibility, and toughness of the solid electrolyte layer or the electrode material layer can be further improved.

[0138] When the polymer contained in the second binder for a solid electrolyte battery contains two or more segments, the configuration of each segment can be the same as the configuration of each segment of the polymer contained in the first binder for a solid electrolyte battery. That is, the polymer contained in the second binder for a solid electrolyte battery can contain segment A and segment B like the polymer contained in the first binder for a solid electrolyte battery, and can have the same configuration as the polymer contained in the first binder for a solid electrolyte battery.

[0139] The polymer contained in the second binder for a solid electrolyte battery can be produced, for example, by the method described above as the method for producing the polymer contained in the first binder for a solid electrolyte battery.

[0140] The first binder for solid electrolyte batteries and the second binder for solid electrolyte batteries (hereinafter sometimes simply referred to as "binders for solid electrolyte batteries") may contain other polymers in addition to the above-mentioned polymers. Examples of the other polymers include fluoropolymers, polymethacrylates, polymethyl methacrylates, polyacrylonitriles, polyimides, polyamides, polyamideimides, polycarbonates, styrene rubbers, butadiene rubbers, styrene butadiene rubbers, and polyacrylic acids.

[0141] The binder for solid electrolyte batteries according to the present disclosure can be suitably used as a material for forming batteries such as secondary batteries and capacitors.

[0142] The present disclosure also relates to the use of a binder containing a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more for forming a solid electrolyte battery. The binder can be particularly suitably used for forming a solid electrolyte layer or an electrode material layer of a solid electrolyte battery.

[0143] The present disclosure also relates to the use of a binder containing a polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount of 5 mass% or less at 25° C., for forming a solid electrolyte battery. The binder can be particularly suitably used for forming a solid electrolyte layer or an electrode material layer of a solid electrolyte battery.

[0144] The solid electrolyte battery may be a primary battery, a storage battery (secondary battery), or a storage element. As the solid electrolyte battery, an all-solid-state lithium ion secondary battery using an inorganic solid electrolyte is preferable. As the solid electrolyte battery, an oxide-based solid battery, a sulfide-based solid battery, etc. can be mentioned. The binder for solid electrolyte batteries of the present disclosure can be suitably used as a binder for solid batteries using an inorganic solid electrolyte, such as a sulfide-based solid battery. As the sulfide-based solid battery, an all-solid-state lithium ion secondary battery using a sulfide-based solid electrolyte as an electrolyte is preferable.

[0145] 3. Slurry The slurry for a solid electrolyte battery of the present disclosure contains the above-mentioned binder for a solid electrolyte battery, a solid electrolyte, and a solvent. Since the slurry of the present disclosure contains the above-mentioned binder for a solid electrolyte battery, the slurry has flexibility that is not significantly inferior to that when a conventional binder is used, and can form a solid electrolyte layer or an electrode material layer that is excellent in adhesion and toughness.

[0146] The slurry for a solid electrolyte battery of the present disclosure is used to form a layer containing a solid electrolyte. The slurry for a solid electrolyte battery of the present disclosure can be used to form a positive electrode material layer containing a solid electrolyte, a solid electrolyte layer containing a solid electrolyte, or a negative electrode material layer containing a solid electrolyte.

[0147] The slurry for solid electrolyte batteries of the present disclosure contains a solid electrolyte, and preferably contains an inorganic solid electrolyte. As the solid electrolyte, a solid electrolyte capable of absorbing and releasing metal ions such as lithium ions can be used. Examples of the solid electrolyte include sulfide-based solid electrolytes, oxide-based solid electrolytes, and crystalline oxides and oxynitrides. In particular, the slurry for solid electrolyte batteries preferably contains a sulfide-based solid electrolyte.

[0148] The sulfide-based solid electrolyte is not particularly limited as long as it is a solid electrolyte containing sulfur atoms, but may be Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x Examples include S4.

[0149] Oxide-based solid electrolytes include LiPON (lithium oxynitride phosphate), Li2O-B2O3-P2O5, Li2O-SiO2, Li 1.3 Al 0.3 Ti 0.7 (PO4)3, La 0.51 Li 0.34 TiO 0.74 , Li3PO4, Li2SiO2, Li2SiO4, Li 0.5 La 0.5 TiO3, Li 1.5 Al 0.5 Ge 1.5 (PO4)3, etc.

[0150] Crystalline oxides and oxynitrides include LiI, Li3N, and Li5La3Ta2O 12, Li7La3Zr2O 12 , Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) N w (w<1), Li 3.6 S 0.6 P 0.4 Examples include O4.

[0151] The slurry for solid electrolyte batteries of the present disclosure contains a solvent. The solvent is preferably a low-polarity solvent. Use of a low-polarity solvent is preferable in that it makes it difficult for the solvent to react with the sulfide-based solid electrolyte. In the present disclosure, a low-polarity solvent is defined as a solvent having a relative dielectric constant of less than 20 at a frequency of 100 kHz. More preferably, it is less than 10.

[0152] The solvent preferably contains at least one compound selected from the group consisting of aromatic compounds, ester compounds, aliphatic hydrocarbon compounds, ether compounds, and carbonate compounds, preferably aromatic compounds and ester compounds, and most preferably ester compounds.

[0153] The low polarity solvent is not particularly limited, and examples thereof include n-octane, n-nonane, n-decane, n-butyl ether, diisopentyl ether, ethylbenzene, ethyl acetate, ethyl butyrate, butyl butyrate, propyl propionate, butyl methacrylate, dimethyl carbonate, diethyl carbonate, methylphenyl ether, cyclopentyl methyl ether, ethylene carbonate, diphenyl ether, fluorobenzene, trifluoromethylbenzene, bistrifluoromethylbenzene, benzene, and thiol.

[0154] Among these, at least one solvent selected from the group consisting of propyl propionate, butyl methacrylate, ethyl acetate, ethyl butyrate, and butyl butyrate can be preferably used as the solvent. A mixed solvent using two or more of these solvents in combination is also acceptable.

[0155] The slurry for solid electrolyte batteries of the present disclosure preferably further contains a conductive assistant, such as carbon black, such as acetylene black or ketjen black; carbon fibers, such as multi-walled carbon nanotubes, single-walled carbon nanotubes, carbon nanofibers, or vapor grown carbon fibers (VGCF); or metal powders, such as SUS powder or aluminum powder.

[0156] The slurry for a solid electrolyte battery of the present disclosure may further contain an electrode active material. The electrode active material may be either a positive electrode active material or a negative electrode active material.

[0157] Examples of the positive electrode active material include LiCoO2, Li(Ni,Co,Al)O2, and Li 1+x Ni 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (x is a real number equal to or greater than 0), LiNiO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, Li3Fe2(PO4)3, Li3V2(PO4)3, Li 1+x Mn 2-x-y M y Li-Mn spinel substituted with different elements having a composition represented by the formula: O4 (M is at least one metal selected from the group consisting of Al, Mg, Co, Fe, Ni, and Zn, and y is a real number of 0 or more), lithium titanate (Li x TiO y ), and lithium metal phosphate having a composition represented by LiMPO4 (M is Fe, Mn, Co, or Ni).

[0158] The positive electrode active materials include LiCoO2, Li(Ni,Co,Al)O2, and LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 is preferred. In the present disclosure, a positive electrode active material in which the surface of each of these materials is coated may be used. The coating material that can be used in the present disclosure may be any material that has lithium ion conductivity and can maintain the shape of the coating layer on the surface of the active material. Examples of coating materials include LiNbO3, Li4Ti5O 12, Li3PO4, etc. The form of the positive electrode active material is not particularly limited, but a powder form is preferable.

[0159] The average particle size of the positive electrode active material is, for example, 1 to 50 μm, preferably 1 to 20 μm, and more preferably 3 to 7 μm. If the average particle size of the positive electrode active material is too small, the handling may become poor, and if the average particle size of the positive electrode active material is too large, it may be difficult to obtain a flat positive electrode material layer. The average particle size of the positive electrode active material can be determined by measuring the particle size of the active material carrier observed by, for example, a scanning electron microscope (SEM) and averaging the measured particle size.

[0160] Examples of the negative electrode active material include carbonaceous materials such as artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon; silicon-containing compounds such as silicon and silicon alloys; and Li4Ti5O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0161] The content of the binder in the slurry for a solid electrolyte battery of the present disclosure is preferably 0.5 to 4.5 parts by mass with respect to 100 parts by mass of the solid content of the slurry for a solid electrolyte battery.

[0162] The solid content concentration of the slurry for a solid electrolyte battery of the present disclosure is preferably 20 to 75 mass %, and more preferably 30 to 70 mass %.

[0163] The method for preparing the slurry for the solid electrolyte battery includes dispersing and mixing the solid electrolyte and, optionally, the electrode active material in a solution or dispersion in which the binder is dissolved or dispersed in a solvent. Alternatively, the binder and the solid electrolyte may be mixed first, and then the solvent may be added to prepare the slurry for the solid electrolyte battery.

[0164] (solid electrolyte layer) The slurry for a solid electrolyte battery of the present disclosure can be used to form a solid electrolyte layer of a solid electrolyte battery. The solid electrolyte layer can be produced, for example, by applying the slurry for a solid electrolyte battery to a transfer sheet, drying the resulting coating, placing the transfer sheet on an electrode material layer so that the coating surface is in contact with the electrode material layer, pressing, and peeling off the transfer sheet.

[0165] Examples of the method for applying the slurry for solid electrolyte batteries to a transfer sheet include spraying, screen printing, doctor blade, bar coating, roll coating, gravure printing, and die coating. Examples of the drying method include vacuum drying, heat drying, and vacuum heat drying. There are no limitations on the specific conditions for vacuum drying and heat drying, and they may be set appropriately.

[0166] 4. Electrode The solid electrolyte battery slurry of the present disclosure can be used to form electrode material layers such as a positive electrode material layer and a negative electrode material layer. The solid electrolyte battery electrode of the present disclosure includes an electrode material layer formed from the above-mentioned solid electrolyte battery slurry. The solid electrolyte battery electrode of the present disclosure can be used as a positive electrode or a negative electrode.

[0167] The electrode of the present disclosure may include only an electrode material layer formed from the above-mentioned slurry for a solid electrolyte battery, or may include a current collector and an electrode material layer formed from the above-mentioned slurry for a solid electrolyte battery. The electrode material layer is formed using the slurry for a solid electrolyte battery of the present disclosure, and may be provided on one side or both sides of the current collector.

[0168] The thickness of the electrode material layer differs depending on the intended use of the solid electrolyte battery, but is preferably 10 to 250 μm, more preferably 20 to 200 μm, and further preferably 30 to 150 μm.

[0169] Examples of the material of the current collector include aluminum, stainless steel (SUS), nickel, iron, titanium, chromium, gold, platinum, zinc, etc., among which aluminum and stainless steel (SUS) are preferred. Examples of the shape of the current collector include foil, plate, mesh, etc., among which foil is preferred.

[0170] The electrode can be produced, for example, by applying the above-mentioned solid electrolyte battery slurry to a current collector and drying the resulting coating. Examples of the coating method include spraying, screen printing, doctor blade, bar coating, roll coating, gravure printing, and die coating. Examples of the drying method include vacuum drying, heat drying, and vacuum heat drying. There are no limitations on the specific conditions for vacuum drying and heat drying, and they may be set appropriately.

[0171] The amount of the slurry for solid electrolyte batteries to be applied varies depending on the composition of the slurry for solid electrolyte batteries and the intended use of the electrodes, but is generally 5 to 30 mg / cm2 in a dry state. 2 The thickness of the electrodes is not particularly limited, but is about 10 to 250 μm.

[0172] 5.Solid electrolyte battery An embodiment of the solid electrolyte battery of the present disclosure includes a positive electrode material layer, a negative electrode material layer, and a solid electrolyte layer formed between the positive electrode material layer and the negative electrode material layer. Also, an embodiment of the solid electrolyte battery of the present disclosure includes a positive electrode including a positive electrode material layer and a current collector, a negative electrode including a negative electrode material layer and a current collector, and a solid electrolyte layer formed between the positive electrode and the negative electrode. In the solid electrolyte battery of the present disclosure, at least one of the positive electrode material layer, the negative electrode material layer, and the solid electrolyte layer is formed from the slurry for a solid electrolyte battery of the present disclosure.

[0173] The solid electrolyte battery may be a primary battery, a storage battery (secondary battery), or a storage element. As the solid electrolyte battery, an all-solid-state lithium ion secondary battery using an inorganic solid electrolyte is preferable. As the solid electrolyte battery, an oxide-based solid battery, a sulfide-based solid battery, etc. are mentioned. As the sulfide-based solid battery, an all-solid-state lithium ion secondary battery using a sulfide-based solid electrolyte as an electrolyte is preferable.

[0174] The solid electrolyte battery of the present disclosure may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0175] The solid electrolyte battery of the present disclosure may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., and examples of the battery case include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0176] The solid electrolyte layer of the present disclosure has excellent adhesion, flexibility, and toughness, and therefore can be suitably used as a solid electrolyte layer for a solid electrolyte battery. Also, the electrode for a solid electrolyte battery of the present disclosure has an electrode material layer with excellent adhesion, flexibility, and toughness, and therefore can be suitably used as an electrode for a solid electrolyte battery.

[0177] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.

[0178] <1> According to a first aspect of the present disclosure, There is provided a binder for solid electrolyte batteries, which contains a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more. <2> According to a second aspect of the present disclosure, There is provided a binder for a solid electrolyte battery according to a first aspect, in which segment A has a heat of fusion of less than 5 J / g, and segment B has a heat of fusion of 5 J / g or more. <3> According to a third aspect of the present disclosure, According to a first or second aspect, there is provided a binder for a solid electrolyte battery, wherein the polymer contains a chain structure represented by general formula (1) or general formula (2). General formula (1):ABA General formula (2): BAB (In the formula, A represents segment A and B represents segment B.) <4> According to a fourth aspect of the present disclosure, There is provided a binder for a solid electrolyte battery according to any one of the first to third aspects, wherein segment A of the polymer contains a fluorine-containing monomer unit. <5> According to a fifth aspect of the present disclosure, According to any one of the first to fourth aspects, there is provided a binder for a solid electrolyte battery, wherein segment A of the polymer contains a vinylidene fluoride unit. <6> According to a sixth aspect of the present disclosure, There is provided a binder for a solid electrolyte battery according to any of the first to fifth aspects, wherein segment A of the polymer contains a vinylidene fluoride unit and at least one selected from the group consisting of repeating units represented by any of the following formulas: Formula:-CF2-CF[-CF3]- Formula:-CH2-CFRf 1 - (In the formula, Rf 1 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms. Formula:-CHF-CHRf 2 - (In the formula, Rf 2 is a linear or branched fluorinated alkyl or fluorinated alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between carbon atoms. <7> According to a seventh aspect of the present disclosure, According to any one of the first to sixth aspects, there is provided a binder for a solid electrolyte battery, wherein segment A of the polymer contains vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units. <8> According to an eighth aspect of the present disclosure, In the binder for solid electrolyte batteries according to any one of the fifth to seventh aspects, there is provided a binder for solid electrolyte batteries, wherein a content of vinylidene fluoride units in segment A of the polymer is 99 to 15 mol % based on all monomer units constituting segment A. <9> According to a ninth aspect of the present disclosure, According to any one of the first to eighth aspects, there is provided a binder for a solid electrolyte battery, wherein segment B of the polymer contains a fluorine-containing monomer unit. <10> According to a tenth aspect of the present disclosure, According to any one of the first to ninth aspects, there is provided a binder for a solid electrolyte battery, wherein segment B of the polymer contains a vinylidene fluoride unit. <11> According to an eleventh aspect of the present disclosure, In a tenth aspect, there is provided a binder for solid electrolyte batteries, wherein a content of vinylidene fluoride units in segment B of the polymer is 97 mol % or more based on all monomer units constituting segment B. <12> According to a twelfth aspect of the present disclosure, Segment B of the polymer is Contains only vinylidene fluoride units, or Contains vinylidene fluoride units and at least one monomer unit selected from the group consisting of tetrafluoroethylene units, hexafluoropropylene units, 2,3,3,3-tetrafluoropropene units, and (meth)acrylic acid units. According to any one of the first to eleventh aspects, there is provided a binder for a solid electrolyte battery. <13> According to a thirteenth aspect of the present disclosure, In the binder for solid electrolyte batteries according to any one of the first to twelfth aspects, a mass ratio (A / B) of segment A to segment B in the polymer is from 40 / 60 to 95 / 5. <14> According to a fourteenth aspect of the present disclosure, The polymer contains a chain structure represented by general formula (1) or general formula (2), General formula (1):ABA General formula (2): BAB (In the formula, A represents segment A and B represents segment B.) Segment A of the polymer is It has a glass transition temperature of -10°C or less, containing vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units in segment A being 18 to 30 mol % based on all monomer units constituting segment A, and the content of the vinylidene fluoride units in segment A being 70 to 82 mol % based on all monomer units constituting segment A, Segment B of the polymer is It has a melting point of 140 to 200°C. Segment B contains vinylidene fluoride units, and the content of the vinylidene fluoride units in Segment B is 97 mol % or more based on all monomer units constituting Segment B; The mass ratio of segment A to segment B in the polymer is 50 / 50 to 90 / 10; The weight average molecular weight of the polymer is 200,000 to 2,000,000. According to any one of the first to thirteenth aspects, there is provided a binder for a solid electrolyte battery. <15> According to a fifteenth aspect of the present disclosure, The binder for solid electrolyte batteries contains a polymer, the polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount of 5 mass% or less at 25°C. <16> According to a sixteenth aspect of the present disclosure, In a fifteenth aspect, there is provided a binder for a solid electrolyte battery, wherein the polymer further contains a vinylidene fluoride unit. <17> According to a seventeenth aspect of the present disclosure, According to a fifteenth or sixteenth aspect, there is provided a binder for a solid electrolyte battery, wherein the polymer contains two or more segments. <18> According to an eighteenth aspect of the present disclosure, The glass transition temperature of the polymer is −10° C. or lower; The melting point of the polymer is 140 to 200°C, the polymer contains vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units being 9 to 24 mol % based on all monomer units constituting the polymer, and the content of the vinylidene fluoride units being 76 to 91 mol % based on all monomer units constituting the polymer; The polymer has a tetrahydrofuran extractable amount of 2 to 4% by mass at 25°C, The weight average molecular weight of the polymer is 200,000 to 2,000,000. According to any one of the fifteenth to seventeenth aspects, there is provided a binder for a solid electrolyte battery. <19> According to a nineteenth aspect of the present disclosure, According to any one of the first to eighteenth aspects, there is provided a slurry for a solid electrolyte battery, comprising a binder for a solid electrolyte battery, a solid electrolyte, and a solvent. <20> According to a twentieth aspect of the present disclosure, According to a nineteenth aspect, there is provided a slurry for a solid electrolyte battery, further comprising an electrode active material. <21> According to a twenty-first aspect of the present disclosure, According to the nineteenth or twentieth aspect, there is provided an electrode for a solid electrolyte battery, comprising an electrode material layer formed from the slurry for a solid electrolyte battery. <22> According to a twenty-second aspect of the present disclosure, According to a twenty-first aspect, there is provided a solid electrolyte battery comprising an electrode. <23> According to a twenty-third aspect of the present disclosure, According to the nineteenth or twentieth aspect, there is provided a solid electrolyte battery comprising a solid electrolyte layer formed from the slurry for a solid electrolyte battery. EXAMPLES

[0179] Next, embodiments of the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0180] The values ​​in the examples were measured by the following methods.

[0181] <Polymer composition> The composition of the fluorocopolymer was measured by solution NMR. Measurement equipment: Varian VNMRS400 Resonance frequency: 376.04 (Sfrq) Pulse width: 30°(pw=6.8)

[0182] <Glass transition temperature (Tg)> A DSC curve was obtained by heating 10 mg of a sample at 20°C / min using a differential scanning calorimeter (DSC822e, Mettler Toledo, or X-DSC7000, Hitachi High-Tech Science). The glass transition temperature was determined as the temperature at the intersection of the extension of the baseline before and after the second-order transition of the DSC curve and the tangent to the inflection point of the DSC curve.

[0183] <Heat of fusion> Using a differential scanning calorimeter (DSC822e, Mettler Toledo, or X-DSC7000, Hitachi High-Tech Science), the sample was heated from 30°C to 220°C at a rate of 10°C / min, and the heat of fusion was calculated from the magnitude of the melting peak (ΔH) of the obtained endothermic curve.

[0184] <Weight average molecular weight> Based on the results of measurement by GPC, the molecular weight was calculated using standard polystyrene as the standard. GPC device: TOSOH HLC-8320GPC Column: 1 SuperAW-H, 3 SuperAWM-H Developing solvent: Dimethylformamide [DMF] Sample concentration: 0.05 mass% Measurement temperature: 40 °C

[0185] <Melting point> Using a differential scanning calorimetry (DSC) apparatus, the temperature corresponding to the peak of the endothermic curve when the sample was heated from 30 °C to 220 °C at a rate of 10 °C / min was determined as the melting point.

[0186] <THF extraction amount> To 1 g of the polymer obtained in each example, 9 g of tetrahydrofuran (THF) was added, and the mixture was stirred at 25 °C using a stirrer. After 24 hours, the solid content was filtered, the solution was dried, and the weight of the dried product was measured to calculate the extraction amount (the ratio of the weight of the dried product to the weight of the polymer (1 g) (mass%)).

[0187] <Maximum test force> In accordance with the method according to ASTM D790, the bending strength (3-point bending test) was measured. A positive electrode having a positive electrode material layer on one side, a negative electrode having a negative electrode material layer on one side, or a laminate containing a solid electrolyte layer was cut into a size of 15 mm × 20 mm to prepare a test piece. In a three-point bending method, the test piece was placed between a first point and a second point at an interval of 10 mm, and the middle (third point) of the test piece was pushed in the thickness direction of the test piece at a constant speed with a probe to perform a bending property test. The force applied while moving at a speed of 5 mm / min in the thickness direction at the third point was measured. The maximum bending strength (maximum bending force or maximum bending strength) is the maximum value of the force applied to the test piece depending on the moving distance of the probe. The comparative example was set to 100 for relative evaluation.

[0188] <Half-width> The bending strength (3-point bending test) was measured according to a method in accordance with ASTM D790. A positive electrode having a positive electrode material layer on one side, a negative electrode having a negative electrode material layer on one side, or a solid electrolyte layer-containing laminate was cut to a size of 15 mm x 20 mm to prepare a specimen. In the 3-point bending method, a specimen was placed between the first and second points, which were spaced 10 mm apart, and a bending property test was performed by pressing the center of the specimen (third point) with a probe in the thickness direction of the specimen at a constant speed. The force applied to the third point was measured while moving at a thickness direction moving speed of 5 mm / min. The maximum bending strength (maximum bending force or maximum bending strength) is the maximum value of the force applied to the specimen depending on the moving distance of the probe. Next, the test force at half the maximum bending strength is calculated, and the distance from the stroke at which the test force reaches half the maximum bending strength when the test force increases after the start of the test to the stroke at which the test force reaches half the maximum bending strength when the test force decreases after reaching the maximum bending strength is the half-width. That is, a curve is drawn with the stroke of the autograph on the horizontal axis and the stress on the vertical axis, and it can be specified as the peak width at half the stress of the peak stress. Comparative Example is set to 100 and the evaluation is performed relative to the above.

[0189] <Adhesion> The adhesion was evaluated by carrying out a 90-degree peel test of the electrode material layer / current collector interface. In the 90-degree peel test, the electrode material layer side of a positive or negative electrode cut to 1.2 x 8.0 cm was fixed to a movable jig, tape was applied to the current collector side, and the stress (N / mm) when the tape was pulled 90 degrees at a speed of 100 mm / min was measured using an autograph. A 1N load cell was used for the autograph. Evaluation was made relative to the comparative example, which was set to 100.

[0190] The following polymers were used in the examples and comparative examples.

[0191] Production example 1 Fluorine-containing copolymer a (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) (Process 1) In a 6L stainless steel autoclave, add 4000ml of pure water, 0.8001g of CH2=CFCF2OCF(CF3)CF2OCF(CF3)COONH450% aqueous solution, and C5F 11 24.021g of COONH450% aqueous solution was added and replaced with nitrogen, then VdF was applied for slight pressure, and the temperature was adjusted to 80°C while stirring at 400 rpm. VdF was injected up to 1.64 MPa, and further VdF and 2,3,3,3-tetrafluoropropylene (R1234yf) mixed monomer with a molar ratio of 77.2 / 22.8 was injected up to 2.001 MPa. 0.16g of ammonium persulfate dissolved in 4ml of pure water was injected with nitrogen to start polymerization. When the mixed monomer reached 24g, 1.009g of 1,4-diiodoperfluorobutane was added. When the pressure dropped to 1.98MPa, the mixed monomer was increased to 2.01MPa, and this was repeated until 1020g was charged. After releasing the gas in the autoclave to 0.05MPa, heat treatment was performed for 3 hours. A 10 g sample of the dispersion in the autoclave was taken and dried to obtain a polymer with a molar ratio of VdF / R1234yf=77.6 / 22.4, a glass transition temperature of -12.5°C, and no heat of fusion.

[0192] (Process 2) After the heat treatment in step 1, the autoclave was kept at 80°C and pressurized to 2.003MPa with VdF, and 0.08g of ammonium persulfate dissolved in 4ml of pure water was pressed in with nitrogen to start polymerization. When the pressure dropped to 1.98MPa, the pressure was increased to 2.01MPa with VdF, and this was repeated until 180g was charged, at which point the gas in the autoclave was released and cooled, and 5270g of dispersion was recovered. The solid content of the dispersion was 23.83% by mass.

[0193] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1250 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=82.0 / 18.0 in molar ratio, and the content of segment B calculated from the composition was 17.2 mass%. The weight average molecular weight Mw was 1,266,000, the glass transition temperature was -12.9°C, the melting point was 160.3°C, and the heat of fusion was 8.2 mJ / mg. The amount of THF extracted was 3 mass%.

[0194] Production example 2 Fluorine-containing copolymer b (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) The same procedure as in Production Example 1 was followed, except that the amount of the mixed monomer charged in step 1 was changed from 1020 g to 900 g, and the amount of VdF charged in step 2 was changed from 180 g to 300 g, to recover 5236 g of a dispersion. The solid content of the dispersion was 24.10 mass%.

[0195] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1257 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=84.2 / 15.8 in molar ratio, and the content of segment B calculated from the composition was 28.1 mass%. The weight average molecular weight Mw was 1,206,000, the glass transition temperature was -11.0°C, the melting point was 161.1°C, and the heat of fusion was 11.0 mJ / mg. The amount of THF extracted was 3%.

[0196] Production example 3 Fluorine-containing copolymer c (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) Except for changing the amount of monomer mixture charged in step 1 from 1020 g to 780 g and changing the amount of VdF charged in step 2 from 180 g to 420 g, the same procedure as in Production Example 1 was followed to recover 5252 g of a dispersion. The solid content of the dispersion was 23.74 mass%.

[0197] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1250 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=85.9 / 14.1 in molar ratio, and the content of segment B calculated from the composition was 36.0 mass%. The weight average molecular weight Mw was 1.29 million, the glass transition temperature was -11.2°C, the melting point was 161.4°C, and the heat of fusion was 17.1 mJ / mg. The amount of THF extracted was 3%.

[0198] Production example 4 Fluorine-containing copolymer d (Preparation of BAB block polymer (wherein A represents segment A and B represents segment B)) (Process 1) In a 6L stainless steel autoclave, add 4000ml of pure water, 0.8003g of CH2=CFCF2OCF(CF3)CF2OCF(CF3)COONH450% aqueous solution, and C5F 11 24.014g of COONH450% aqueous solution was added and replaced with nitrogen, then VdF was slightly pressurized, and the temperature was adjusted to 80°C while stirring at 400 rpm, and VdF was pressed in up to 2.00 MPa. 0.16g of ammonium persulfate dissolved in 4ml of pure water was pressed in with nitrogen to start polymerization. When the pressure reached 24g of VdF, 1.009g of 1,4-diiodoperfluorobutane was added. When the pressure dropped to 1.98MPa, it was increased to 2.01MPa with VdF, and this was repeated until 300g was charged, after which the gas in the autoclave was released to 0.05MPa, and heat treatment was performed for 3 hours. 10g of the dispersion in the autoclave was sampled and dried to obtain a polymer whose glass transition temperature was not visible, its melting point was 161.1°C, and its heat of fusion was 44.8mJ / mg.

[0199] (Process 2) After the heat treatment in step 1, the autoclave was kept at 80°C, and the pressure was increased to 1.64MPa with VdF and 2.001MPa with a mixed monomer solution of VdF and R1234yf with a molar ratio of 77.5 / 22.5, and 0.08g of ammonium persulfate dissolved in 4ml of pure water was added with nitrogen to start polymerization. When the pressure dropped to 1.98MPa, the mixed monomer solution was increased to 2.01MPa, and this was repeated until 900g was added, at which point the gas in the autoclave was released and cooled, and 5271g of dispersion was recovered. The solid content of the dispersion was 23.80% by mass.

[0200] Aluminum sulfate was added to this dispersion to cause coagulation, and then dried to obtain 1248 g of polymer. The composition of the obtained block polymer was VdF / R1234yf=82.7 / 17.3 in molar ratio, and the content of segment B calculated from the composition was 24.1 wt%. The weight average molecular weight Mw was 1,426,000, the glass transition temperature was -10.4°C, the melting point was 160.8°C, and the heat of fusion was 10.8 mJ / mg. The amount of THF extracted was 3 mass%.

[0201] Production example 5 Fluorine-containing copolymer e According to the manufacturing method described in Example 12 of JP 2013-216915, a fluoroelastomer with a molar ratio of VdF and R1234yf of 78.6 / 21.4 was obtained. There was no heat of fusion. The amount of THF extracted was 100% by mass.

[0202] Examples 1 to 12 and Comparative Examples 1 to 3 (Preparation of binder solution) As a binder, the polymer shown in Table 1 was added to butyl butyrate, and the mixture was stirred overnight at 50° C., followed by three repeated ultrasonic treatments (90 seconds) using an ultrasonic homogenizer to prepare a binder solution. Here, the binder was contained at 5% by mass, with the entire binder solution being 100% by mass.

[0203] In the present disclosure, a positive electrode, a negative electrode slurry, and a solid electrolyte layer were prepared in the following procedure.

[0204] (1) The binder solution obtained by the above-mentioned method and a separately prepared active material (positive electrode active material or negative electrode active material) or a sulfide-based solid electrolyte are added to butyl butyrate, and a dispersion treatment (e.g., ultrasonic treatment) is performed to obtain a "positive electrode active material-binder slurry," "negative electrode active material-binder slurry," or "solid electrolyte-binder slurry" in which the active material or sulfide-based solid electrolyte and binder are highly dispersed in a low-polarity solvent.

[0205] (2) A sulfide-based solid electrolyte or an active material (positive electrode active material or negative electrode active material) is added to the "positive electrode active material / binder slurry," "negative electrode active material / binder slurry," or "solid electrolyte / binder slurry" obtained in (1) and a dispersion process (e.g. ultrasonic treatment) is carried out to obtain a "positive electrode slurry" or "negative electrode slurry" in which the active material, sulfide-based solid electrolyte, and binder are highly dispersed in the solvent. A more specific method for producing the slurry is shown below.

[0206] (Preparation of negative electrode slurry) The binder solution thus prepared was used to prepare negative electrode slurries according to the examples and comparative examples, as detailed below.

[0207] The binder solution, graphite as the negative electrode active material, and butyl butyrate were added to a PFA container, and ultrasonic treatment (50 seconds) was performed once using an ultrasonic homogenizer to prepare a "negative electrode active material-binder slurry." The binder solution, butyl butyrate, and sulfide-based solid electrolyte (30LiI·70(0.75Li2S·0.25P2S5)) were further added to the obtained negative electrode active material-binder slurry, and ultrasonic treatment (30 seconds) was performed three times using an ultrasonic homogenizer to obtain a "slurry for negative electrode" in which the negative electrode active material, sulfide-based solid electrolyte, and binder were highly dispersed. The final solid concentration of the active material binder in the slurry was 3.0 mass%.

[0208] (Preparation of negative electrode) Each negative electrode slurry was applied onto a copper foil negative electrode current collector using a doctor blade and dried to obtain a negative electrode having a negative electrode material layer of 110 μm in thickness formed on the surface of the negative electrode current collector.

[0209] (Preparation of Positive Electrode Slurry) The prepared binder solution was used to prepare slurries for positive electrodes according to the examples and comparative examples. Specifically, the procedures are as follows.

[0210] In a PFA container, put the above binder solution and the ternary active material Li(NiMnCo) as the positive electrode active material. 1 / 3 Butyl butyrate was added together with O2, and ultrasonic treatment (50 seconds) was performed once using an ultrasonic homogenizer to prepare a "positive electrode active material / binder slurry." The obtained positive electrode active material / binder slurry was further added with a binder solution, butyl butyrate, and a sulfide-based solid electrolyte (30LiI·70(0.75Li2S·0.25P2S5)), and ultrasonic treatment (30 seconds) was performed three times using an ultrasonic homogenizer to obtain a "positive electrode slurry" in which the positive electrode active material, sulfide-based solid electrolyte, and binder were highly dispersed. The final binder solid concentration in the slurry was 3.0 mass%.

[0211] (Preparation of positive electrode) Each positive electrode slurry was applied onto an aluminum foil current collector using a doctor blade and dried to obtain a positive electrode having a positive electrode material layer of 85 μm in thickness formed on the surface of the positive electrode current collector.

[0212] (Preparation of solid electrolyte layer) An electrolyte slurry was prepared using butyl butyrate, the above-mentioned sulfide-based solid electrolyte as a solid electrolyte, and a binder solution, and the prepared electrolyte slurry was applied to a peelable substrate (aluminum foil) using a doctor blade, and then dried to form a solid electrolyte layer having a thickness of 45 μm on the substrate. The mass ratio of the solid electrolyte and the binder in the solid electrolyte layer was solid electrolyte: binder = 100 parts by mass: 1 part by mass. A laminate (sometimes referred to as a "solid electrolyte layer-containing laminate" in this disclosure) including a solid electrolyte layer and a substrate (aluminum foil) was used to measure the maximum test force and half-width.

[0213] The electrolyte slurry was prepared as follows. The solid electrolyte and binder solution were added to the solvent butyl butyrate, and ultrasonic treatment (30 seconds) was performed once using an ultrasonic homogenizer to obtain an electrolyte slurry in which the solid electrolyte and binder were highly dissolved or dispersed. The solid content at this time was 39%.

[0214] The results are shown in Table 1.

[0215] [Table 1]

Claims

1. A binder for a solid electrolyte battery, comprising a polymer including a segment A having a glass transition temperature of 25° C. or less and a segment B having a melting point of 50° C. or more.

2. 2. The binder for a solid electrolyte battery according to claim 1, wherein segment A has a heat of fusion of less than 5 J / g, and segment B has a heat of fusion of 5 J / g or more.

3. 3. The binder for a solid electrolyte battery according to claim 1, wherein the polymer contains a chain structure represented by general formula (1) or general formula (2). General formula (1): ABA General formula (2): B-A-B (In the formula, A represents segment A and B represents segment B.)

4. 3. The binder for a solid electrolyte battery according to claim 1, wherein the segment A of the polymer contains a fluorine-containing monomer unit.

5. 3. The binder for a solid electrolyte battery according to claim 1, wherein the polymer segment A contains a vinylidene fluoride unit.

6. 3. The binder for a solid electrolyte battery according to claim 1, wherein the polymer segment A contains at least one repeating unit selected from the group consisting of a vinylidene fluoride unit and a repeating unit represented by any one of the following formulae: Formula: -CF 2 -CF[-CF 3 - Formula: -CH 2 -CFR 1 - (wherein, Rf 1 is a linear or branched fluorinated alkyl or alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between the carbon atoms. Formula: -CHF-CHRR 2 - (wherein, Rf 2 is a linear or branched fluorinated alkyl or alkoxy group having 1 to 12 carbon atoms, and when it has 2 or more carbon atoms, it may contain an oxygen atom between the carbon atoms.

7. 3. The binder for a solid electrolyte battery according to claim 1, wherein the polymer segment A contains a vinylidene fluoride unit and a 2,3,3,3-tetrafluoropropene unit.

8. 6. The binder for solid electrolyte batteries according to claim 5, wherein the content of vinylidene fluoride units in the segment A of the polymer is 99 to 15 mol % based on the total monomer units constituting the segment A.

9. 3. The binder for a solid electrolyte battery according to claim 1, wherein the segment B of the polymer contains a fluorine-containing monomer unit.

10. 3. The binder for a solid electrolyte battery according to claim 1, wherein the segment B of the polymer contains a vinylidene fluoride unit.

11. 11. The binder for a solid electrolyte battery according to claim 10, wherein the content of vinylidene fluoride units in the segment B of the polymer is 97 mol % or more based on all monomer units constituting the segment B.

12. Segment B of the polymer is Contains only vinylidene fluoride units, or Contains vinylidene fluoride units and at least one monomer unit selected from the group consisting of tetrafluoroethylene units, hexafluoropropylene units, 2,3,3,3-tetrafluoropropene units and (meth)acrylic acid units. The binder for a solid electrolyte battery according to claim 1 or 2.

13. 3. The binder for solid electrolyte batteries according to claim 1, wherein a mass ratio (A / B) of segment A to segment B in the polymer is 40 / 60 to 95 / 5.

14. The polymer contains a chain structure represented by general formula (1) or general formula (2), General formula (1): ABA General formula (2): B-A-B (In the formula, A represents segment A and B represents segment B.) Segment A of the polymer is It has a glass transition temperature of −10° C. or less, containing vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units in segment A being 18 to 30 mol % based on all monomer units constituting segment A, and the content of the vinylidene fluoride units in segment A being 70 to 82 mol % based on all monomer units constituting segment A, Segment B of the polymer is It has a melting point of 140 to 200°C, Segment B contains vinylidene fluoride units, and the content of the vinylidene fluoride units in Segment B is 97 mol % or more based on all monomer units constituting Segment B; The mass ratio of segment A to segment B in the polymer is 50 / 50 to 90 / 10; The weight average molecular weight of the polymer is 200,000 to 2,000,000. The binder for a solid electrolyte battery according to claim 1 or 2.

15. A binder for solid electrolyte batteries containing a polymer, the polymer having a glass transition temperature and a melting point, containing 2,3,3,3-tetrafluoropropene units, and having a tetrahydrofuran extractable amount at 25° C. of 5 mass % or less.

16. The binder for a solid electrolyte battery according to claim 15, wherein the polymer further contains a vinylidene fluoride unit.

17. The binder for a solid electrolyte battery according to claim 15 or 16, wherein the polymer contains two or more segments.

18. The glass transition temperature of the polymer is −10° C. or lower; The melting point of the polymer is 140 to 200° C., the polymer contains vinylidene fluoride units and 2,3,3,3-tetrafluoropropene units, the content of the 2,3,3,3-tetrafluoropropene units being 9 to 24 mol % based on all monomer units constituting the polymer, and the content of the vinylidene fluoride units being 76 to 91 mol % based on all monomer units constituting the polymer; The polymer has a tetrahydrofuran extractable amount of 2 to 4% by mass at 25° C.; The weight average molecular weight of the polymer is 200,000 to 2,000,000. The binder for a solid electrolyte battery according to claim 15 or 16.

19. A slurry for a solid electrolyte battery, comprising the binder for a solid electrolyte battery according to claim 1 or 15, a solid electrolyte, and a solvent.

20. The slurry for a solid electrolyte battery according to claim 19, further comprising an electrode active material.

21. An electrode for a solid electrolyte battery comprising an electrode material layer formed from the slurry for a solid electrolyte battery according to claim 19.

22. A solid electrolyte battery comprising the electrode according to claim 21.

23. A solid electrolyte battery comprising a solid electrolyte layer formed from the slurry for a solid electrolyte battery according to claim 19.

Citation Information

Patent Citations

  • BAB type block copolymer, preparation method, binder, positive pole piece, secondary battery and electric device

    CN115286805A

  • Solid electrolyte molding body, electrode molding body, and electrochemical element

    JP2000123874A

  • functionalized fluorinated copolymer

    JP2018530662A

  • solid polymer electrolyte

    JP2021514095A

  • Binder, slurry for solid-state batteries, electrode for solid-state batteries, and solid-state secondary battery

    WO2021015229A1